Surfactant-assisted imidacloprid intercalation of layered zinc hydroxide nitrate:synthesis, characterisation and controlled resease formulation - Norhayati Hashim (Tanjong Malim, 2019)
Surfactant-assisted imidacloprid intercalation of layered zinc hydroxide nitrate:synthesis, characterisation and controlled resease formulation by Norhayati Hashim